High-energy particle interactions in the inner jet of the radio galaxy M87 - Guennou, Chloé (2010)
Recent observations with the High Energy Stereoscopic System (HESS) have revealed strong and variable high-energy gamma-ray emission from the radio galaxy M87. The origin of such emission is uncertain, but the rapid variability indicates that it should be produced close to the central engine of the source. In this work, a lepto-hadronic one-zone model is applied to the available multiwavelength data of M87. The different energy losses for both primary and secondary particles are calculated. Then, the different contributions to the spectral energy distribution through interactions with matter, radiation and magnetic fields are obtained, in good accordance with the observations.